INFLUENCE OF EMOTIONAL INTELLIGENCE, AND SELF DETERMINATION OF STATISTICS ALEARNING OUTCOME - Emma Rumahlewang (International Journal of Advanced Science and Technology, 2020)
The objective of this research were to know the influence of self-concept, emotional intelligence toward student’s statistics achievement in teacher training and education faculty of Pattimura University. The method of this research was survey method. The respondents in this research were 220 students of teacher training and education faculty. Data were collected by using questionnaire about self-concept, emotional intelligence, while the data of statistics achievement were collected by using assessment rubric. The data were analyzed by using path analysis. The result of this research were there are a direct positive relation between self-concept, emotional intelligence, toward student’s statistics achievement.